Estimating electrical properties and the thickness of skin with electrical impedance spectroscopy: Mathematical analysis and measurements - Birgersson U. (Journal of Electrical Bioimpedance, 2012)
Electrical impedance spectroscopy (EIS) allows for the study and characterization of tissue alterations and properties associated with the skin. Here, the potential application of EIS to estimate the thickness of the stratum corneum is explored in the form of a mathematical model for EIS, which is analyzed in the limit of 1 kHz and closed-form analytical solutions derived. These analytical expressions are verified with the numerical solution of the full set of equations and validated with an EIS study comprising 120 subjects: overall, good agreement is found in the frequency range 1-100 kHz, where the impedance is governed by the stratum corneum. Combining the closed-form expression for the thickness of the stratum corneum predicted by the model with the experimental EIS measurements, a distribution for the stratum corneum thickness of the subjects is found with a mean and standard deviation that agree well with reported stratum corneum thicknesses from other experimental techniques. This, in turn, suggests that EIS could be employed to measure the thickness of the stratum corneum with reasonable accuracy. In addition, the electrical properties relevant to EIS – conductivity and relative permittivity – of the stratum corneum can be estimated with the closed form expressions if the stratum corneum thickness is known.